SINDRUM R2 DALAM ANALISIS REGRESI LINIER RUNTUN WAKTU - Insukindro Insukindro (Faculty of Economics and Business, Universitas Gadjah Mada, 1998)
This paper attempts to discuss the coefficient of determination (R) in time series econometric analysis. The coefficient is the most commonly used measure of the goodness of fit of a regression line. With time series data high R values can be obtained if the linear regressions are estimated with the level. Therefore, there is a strong tendency to estimate the time series model in levels rather than, for example, in first differences. In general, researchers associate a high R2 with a good fit and it can be considered as indicative of a strong ability of the independent variables to